A Comparison Between Visual Imagery Strategy and Conventional Strategy in The Teaching of English For Science - Noordin, Nooreen (2004)
The main purpose of the study was to investigate and compare the effectiveness between visual imagery strategy and conventional strategy in the teaching of English for Science and Technology. A total of 89 students (n=89) were assigned to two groups, where each group underwent three phases of the experiment - 1) Pre-test Phase, 2) Treatment Phase, and 3) Post-test Phase. In this study, visual imagery strategy was a teaching procedure that incorporated the use of visuals and the forming of images that suggested the kind of representations students need to conjure within the context of the topic being taught. Conventional strategy was the teaching method prescribed by the English teacher in which students' attention were directed to important facts and concepts pertaining to the topic. Evaluation to ascertain students' le'ariing achievement was based on their pre-test and post-test scores obtained as participants performed the Language Achievement test, which included evaluation on reading comprehension and writing skills. Analysis was also done on their language functions, vocabulary tasks, reading comprehension, and essay writing skills from the science- and technical-based lessons taught to the students. The results of the study was reported in accordance with the hypotheses developed which compared the effectiveness between visual imagery strategy and conventional strategy on dependent variables such as reading comprehension achievement, writing skills and vocabulary achievement, as well comparing the effectiveness between the two strategies used among low English proficiency and high English proficiency students. Data analysis indicated that visual imagery strategy produced significant main effect on students' total reading comprehension and writing achievement, as compared to conventional strategy (F(1,84) = 17.55, p < .000), but there was no significant interaction effect between proficiency level and type of treatment applied (F(1,84) = .895, p > .347, with a very small effect size (eta squared = .011). Based on reading comprehension scores alone, it was found that visual imagery strategy produced significant main effect on students' reading comprehension achievement, as compared to conventional strategy (F(1,84) = 14.03, p < .000; eta squared = .143), but again, there was no significant interaction effect between proficiency level and type of treatment applied (F(1,84) = .002, p > .620; eta squared = .010). Based on writing scores alone, it was found that visual imagery did not produce significant main effect on students' writing achievement as compared to conventional strategy(F(l,84) = 1.27, p = .261). However, there was significant interaction effect between proficiency level and the treatments applied in determining students' writing achievement (F(1,84) = 1.06, p < .041, with a small effect size (eta squared = .012). Data analysis also indicated that visual imagery strategy (M=9.93, SD=2.98) did not produce significant differential effect on students' vocabulary skills performance during the treatment phase, as compared to the conventional strategy: (M=9.37, SD=3.51; t(87)=.802, p=.425). Students' responses regarding their knowledge and perception of visual imagery strategy and its application on teaching reading comprehension and writing skills in English for Science and Technology also favored the use of visuals and imagery instructions. Lastly, it was found that students agree that visual imagery strategy should be incorporated in English for Science and Technical lessons as it helped students understand scientific and technical passages better during reading-instruction. The implication of the study suggests that visual imagery strategy can be beneficial for students learning English for Science and Technology as the strategy promoted the recall of previous knowledge and provided interaction with the content. Visual imagery strategy as a teaching method should be utilized to its full potential, as it can be beneficial in facilitating the teaching and learning of English for science and technical reading comprehension and other language skills.